2019
DOI: 10.1108/ijccsm-02-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 2015 El Nino on smallholder maize production in the transitional ecological zone of Ghana

Abstract: Purpose -This paper aims to provide empirical evidence on the El Nino and its effects on maize production in three municipalities: Ejura, Techiman and Wenchi in the transitional zone of Ghana. Using a mixed approach, the study details the effects of the El Nino on rainy season characteristics, particularly, rainfall amounts and distribution, onset and cessation of rains, duration of the rainy season and total seasonal rainfall and how it impacted smallholder maize production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Rainfed food crop production is the critical source of livelihood in Southern Africa (Mavhura, Manatsa & Mushore 2015 ). Outside the Southern African region, Owusu et al ( 2019 ) reported crop failure and poor harvest in Ghana because of the 2015–2016 El Niño-induced drought. They also reported that ‘The major impacts of the El Nino induced rainfall failure and yield reduction were household food insecurity, loss of income, indebtedness and deepening poverty’ (Owusu et al 2019 :618).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainfed food crop production is the critical source of livelihood in Southern Africa (Mavhura, Manatsa & Mushore 2015 ). Outside the Southern African region, Owusu et al ( 2019 ) reported crop failure and poor harvest in Ghana because of the 2015–2016 El Niño-induced drought. They also reported that ‘The major impacts of the El Nino induced rainfall failure and yield reduction were household food insecurity, loss of income, indebtedness and deepening poverty’ (Owusu et al 2019 :618).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Outside the Southern African region, Owusu et al ( 2019 ) reported crop failure and poor harvest in Ghana because of the 2015–2016 El Niño-induced drought. They also reported that ‘The major impacts of the El Nino induced rainfall failure and yield reduction were household food insecurity, loss of income, indebtedness and deepening poverty’ (Owusu et al 2019 :618). In Zimbabwe, the impact was significant because 70% of the food production is dependent on peasant agriculture (FAO 2016 ) and more than 80% of the rural households have no access to water for irrigation purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, crops are more likely to do well under uniformly distributed "light rain" conditions over a long period compared to few "heavy" rainfall events interspersed by recurring dry spells. Owusu, Ayisi, Musah-Surugu and Yankson [7] reported that, because in Ghana maize is often cultivated under rain-fed conditions, it is extremely vulnerable to climate extremes such as prolonged droughts. Evidence from the present study shows that increased dry spells, in terms of either longevity or frequency, pose a major risk to maize production in the transition zone of Ghana, and thus threaten its status as the breadbasket of the nation.…”
Section: Drivers Of Maize Production Failure In 2020mentioning
confidence: 99%
“…Despite the efforts to improve maize yield, challenges such as fall armyworm (Spodoptera frugiperda) infestation and extreme rainfall events have debilitated productivity in recent years. For instance, in 2016, a severe El Niño led to a drastic reduction in maize yield [7]. Similarly, between late 2020 and the middle of 2021, Ghana went through a serious maize grain crisis emanating from the 2020 minor season crop failure.…”
Section: Introductionmentioning
confidence: 99%